The heteromorph ammonite Ndumuiceras variabile gen. et sp nov from the Albian Mzinene Formation, KwaZulu-Natal, South Africa - Kennedy, W; Klinger, H (2009)
Four specimens of a micromorphic heteromorph ammonite, one from the Lower Albian Mzinene Formation in the vicinity of Ndumu, and three from the basal Middle Albian Mzinene Formation in the Mkuze Game Reserve of KwaZulu-Natal are referred to the new genus and species Ndumuiceras variabile. Its general appearance suggests affinities with the crioceratitid representatives of the superfamily Ancyloceratoidea Gill, 1871, but the suture line points to affinities with the superfamily Turrilitoidea Gill, 1871.